Morphological characteristics of Phaius spp. orchids from Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hartati S, Samanhudi, Manurung IR, Cahyono O. 2021. Morphological characteristics of Phaius spp. orchids from Indonesia. Biodiversitas 22: 1991-1995. Orchid is one of the ornamental plants with great economic value in various communities. Characterization and grouping of several orchid species can be used in breeding efforts to obtain hybrid with the desired traits. This study is aimed to characterize the morphological appearance of Phaius orchids and to cluster the species based on their similarity in morphological characteristics. Five species of Phaius (P. tankervilleae, P. indigoferus, P. montanus, P. amboinensis, and P. callosus) of the collection of the Bogor Botanical Garden were observed based on 30 morphological characters including the characters of stems, pseudobulbs, leaves and flowers. The data obtained were converted into binary data and computed using the Numerical Taxonomy and Multivariate Analysis System (NTSYS) Spc 2.02 program to produce dendrogram. The results show that based on the morphological characterization of the five species of Phaius spp., they have similarities from 63% to 80%. Among the five Phaius species, P. amboinensis, P. tankervilleae, and P. montanus had 80% similarity and can be used as parents for crossing.
Keywords: Characterization, morphological, Phaius, orchids, similarity